RATIO TOTAL BENCHMARKING SESUAIKAH DENGAN KONDISI WAJIB PAJAK? (Studi pada Empat Perusahaah Rokok yang Terdaftar di BEI) - Theresia Woro Damayanti; Eko Sukmono Adiritonga (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
Ratio of total benchmarking issued by the director general on the basis of his tax is a referencecomparator in determining the reasonableness of the fairness of the tax reporting companies (tax payers).This study aims to analyze the uses of total ratio benchmarking methods in determining fairness of thefinancial performance of the cigarette companies are listed on BEI. The research was carried out oncigarette companies listed on Bursa Efek Jakarta (BEI).Results showed that there is a difference between the ratio of total benchmarking on cigarettecompanies listed on the stock exchange compare to the reference ratio of total banchmarking who issuedby the director general of tax. Calculations based on the ratio of the thirteen benchmarks show that thereare many differences in any ratio compared with the reference benchmark ratio of total tax incurred by thedirector general.